AIAA Scitech 2019 Forum 2019
DOI: 10.2514/6.2019-0001
|View full text |Cite
|
Sign up to set email alerts
|

Noise Amplification Effects due to Jet-Surface Interaction

Abstract: A numerical investigation on jet-installation noise is performed using a software based on the Lattice-Boltzmann Method. A flat plate is placed in the irrotational hydrodynamic field of the jet, i.e. outside of the plume, resulting in noise increase due to the scattering of instability waves at the plate trailing edge. The configuration adopted in this work replicates the one used for a benchmark study at NASA Glenn, against which the numerical results are validated. Far-field noise spectra from the isolated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…6 Rego et al. 7 used Lattice-Boltzmann method to study noise amplification effects due to jet-surface interaction. On the experimental side Head and Fisher 8 and Brown and Ahuja 9 observed that the noise reduction or increase due to interaction with the airframe depends on which radiation side the observer is located.…”
Section: Introductionmentioning
confidence: 99%
“…6 Rego et al. 7 used Lattice-Boltzmann method to study noise amplification effects due to jet-surface interaction. On the experimental side Head and Fisher 8 and Brown and Ahuja 9 observed that the noise reduction or increase due to interaction with the airframe depends on which radiation side the observer is located.…”
Section: Introductionmentioning
confidence: 99%
“…Rego et al [18] utilized a Lattice-Boltzmann Method (LBM) to carry out numerical simulations of a flat plate placed in an irrotational hydrodynamic field of a jet with a round nozzle. Three cases were investigated with input flow characteristics determined from NASA wind tunnel experiments (see Brown [19]).…”
Section: Introductionmentioning
confidence: 99%